Parametric study of an integral abutment bridge supported by prestressed precast concrete piles. (1st August 2016) - Kong, B.; Cai, C.S.; Zhang, Y.
Highlights: Present a parametric investigation on the bridge's performance under different conditions. Proposed numerical modeling methodology is validated by field measurements. The behavior of IABs is observed greatly affected by the temperature loadings. Appropriate design method for IABs can accommodate the temperature induced effects. Abstract: Integral abutment bridges (IABs) have been designed and constructed since the 1930s around the world. In these bridges, the water leaking problems and maintenance issues of expansion joints are minimized. However, the behaviors of IABs under temperature effects have not been completely understood. In the state of Louisiana, the first full IAB, i.e., the Caminada Bay Bridge, was built on the soft soil conditions in 2011. This paper presents a numerical investigation on the thermal performance of this bridge using ANSYS software. Based on the analysis studies, the numerical modeling methodology for IABs, i.e., temperature loadings, backfill–abutment interactions, and soil–pile interactions, is validated by comparing the bridge response with the field measurements. In addition, a parametric study is performed and demonstrated that the behavior of IABs is affected by temperature loadings, boundary support types, backfills behind abutments, soils surrounding piles, and pile–bent connections. It needs to balance all these parameters in designs so that the thermal deformation of slabs is appropriately accommodated without compromising the integrity of the superstructure and substructure.